1981
DOI: 10.1139/e81-137
|View full text |Cite
|
Sign up to set email alerts
|

Regional stratigraphy and structural setting of the Kamloops Group, south-central British Columbia

Abstract: The Kamloops Group is redefined as an assemblage of Lower to Middle Eocene volcanic and sedimentary rocks widespread in south-central British Columbia. In the type area west of Kamloops, the basal Tranquille Formation consists of 500 m of lacustrine and deltaic sediments, pillowed flows, and hyaloclastites. Elsewhere, basal coal-bearing nonvolcanic fluvial and lacustrine units occur, such as the Coldwater Formation at Merritt, the Chu Chua Formation at Barriere, and the Shorts Creek Formation west of Vernon. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 13 publications
2
48
0
Order By: Relevance
“…The shale beds are capped by flow breccia and sit atop an ash-flow tuff. Tephra deposits bracketed by fossiliferous layers yielded K-Ar dates of 49 ± 2 and 52 ± 2 Ma from plagioclase and 51 ± 2 Ma from biotite contained within a bentonitic tuff (Ewing 1981). These dates generally support the interpretation of a late Early Eocene age.…”
Section: Geology and Age Of Depositssupporting
confidence: 62%
“…The shale beds are capped by flow breccia and sit atop an ash-flow tuff. Tephra deposits bracketed by fossiliferous layers yielded K-Ar dates of 49 ± 2 and 52 ± 2 Ma from plagioclase and 51 ± 2 Ma from biotite contained within a bentonitic tuff (Ewing 1981). These dates generally support the interpretation of a late Early Eocene age.…”
Section: Geology and Age Of Depositssupporting
confidence: 62%
“…Ottawa collections from Chu Chua are catalogued under four main locality numbers corresponding to the separate areas of outcrop from which Berry (1926) described taxa. Ewing (1981) refers coal-bearing sediments in this area to the Early Eocene Chu Chua Formation, noting similarities to the Coldwater beds near Merritt that include the Quilchena flora. Wolfe et al (1998) suggested an age of 48-50 Ma for the Chu Chua flora (Fig.…”
Section: Horsefly Rivermentioning
confidence: 99%
“…These deposits formed after the geological processes described below: Extensive strikeslip faulting occurred in northeast Washington during the late early to early middle Eocene. During this time, the southern Cordillera of northernmost central Washington, and up into south-central British Columbia, experienced episodes of right-lateral faulting responsible for producing a set of northwest-trending grabens and half-grabens (Ewing 1981, Matthews 1991, Mustoe 2005. A volcanic arc in south-central British Columbia provided a source of large volumes of volcaniclastic sediments and basalt flows in these basins.…”
Section: The Okanogan Highlandsmentioning
confidence: 99%